Systemic Cystic Angiomatosis Mimicking Metastatic Cancer: A Case Report and Review of the Literature - Vivek Kumar; Trishala Meghal; Yanyu Helen Sun; Yiwu Huang (Case Reports in Medicine)
Systemic cystic angiomatosis is a rare benign disorder due to the maldeveloped vascular and lymphatic system with less than 50 cases reported in literature so far. We report here a case of systemic cystic angiomatosis (SCA) with multisystem involvement affecting the neck, thyroid, thoracic cavity, and skeletal system. The patient initially presented in her 4th decade of life with isolated lymphangioma in the neck requiring surgery. However, she experienced full-blown manifestations of SCA in her 6th decade which closely mimicked metastatic cancer. The diagnosis of SCA could only be established after multiple biopsies. The radiological and histological features of SCA with its course over 31 years in this patient have been described.